A Quality Improvement Project to Improve First Case On-time Starts in the Pediatric Operating Room. Issue 4 (July 2020) - Pashankar, Dinesh S.; Zhao, Anna M.; Bathrick, Rebecca; Taylor, Cindy; Boules, Heidi; Cowles, Robert A.; Grossman, Matthew
Abstract : Background: Delays in the operating room (OR) can lead to increased hospital costs as well as patient and provider dissatisfaction. Starting the first case on time in the OR can potentially prevent subsequent delays. We designed a quality improvement project to improve the first case on-time starts in the pediatric OR at a tertiary care children's hospital. Methods: Following the collection of baseline data, we formed an interdisciplinary team. We analyzed the causes of delay and used the Six Sigma methodology of Define, Measure, Analyze, Improve, and Control. We identified key drivers and implemented several low-cost interventions using Plan-Do-Study-Act cycles. Major interventions included preoperative care coordination, strategic staggering of OR cases, and introduction of "Wow Bucks" incentives. We monitored start times and the delay in minutes for all first cases weekly. The OR minutes saved per week were calculated and used to estimate cost savings. Results: We studied a total of 1981 first-start cases from May 2018 to October 2019. The first case on-time starts improved from 62% to 77% over the study period. There was a significant improvement in total minutes delayed for all the first cases from 197.9 minutes per week down to 133 minutes per week ( P < 0.05). Estimated cost savings were 4, 023 per week due to improved OR utilization. Conclusions: A multidisciplinary collaborative team approach using quality improvement tools can improve on-time starts in the pediatric OR.